Hambatan pengoperasian variabel teknis Pemilu terhadap keterwakilan perempuan di DPR - Talaba, Renals Y. (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2024)
The low representation of women in the Indonesian DPR (People's Consultative Assembly) indicates a problem with the electoral system. Women's concerns cannot be translated into policy if they are not directly involved in decision-making. The study aims to identify the factors that contribute to the low representation of women in the DPR, specifically examining the operation of indirect and direct election technical variables. The research uses a literature review approach to understand the concepts of the electoral system, democracy, the party system, and affirmation policies. The findings reveal that the affirmation policy, which focuses primarily on the election formula, is insufficient to guarantee women's representation in the DPR. Other technical variables are considered detrimental to women's representation. Despite the implementation of the affirmation policy, the number of women in the DPR has not reached a critical mass from the 2004 to 2019 elections.